FRI0348 USE OF INTRAVENOUS IMMUNOGLOBULIN THERAPY IN PATIENTS WITH SYSTEMIC SCLEROSIS: A SPANISH MULTICENTER EXPERIENCE. (June 2019) - TANDAIPAN JAIME, Jose Luis; Castillo, Alfredo Guillén del; Simeón-Aznar, Carmen Pilar; Carreira, Patricia; Narváez, J.; Pego-Reigosa, Jose M.; Vicuna, Rosario Garcia de; Pros, Anna; Bujidos, Carlos De la Puente; Ortiz-Santamaria, Vera; Atienza-Mateo, Belén; Lluch Pons, J; et al.
Abstract : Objectives: To describe the efficacy of intravenous immunoglobulin (IVIG) therapy in different organic conditions of Systemic Sclerosis (SSc). Methods: Retrospective multicenter observational study that enrolled patients with SSc treated with IVIG. We collected epidemiological data, SSc complications, treatments and functional tests. Regarding IVIG treatment we recorded the reason to use, number of cycles, and the clinical efficacy at the end of the last IVIG cycle were collected at investigator's discretion. For the comparison of variables, the Chi-square, Fisher's F test and the T test was used. Results: 41 patients (83% women) were recruited, with a mean age of 58 ± 18.2 years old. The age of diagnosis was 48 ± 8 years old. The diffuse cutaneous SSc was the most frequent in the sample (61%) and 24/41 had Overlap syndrome (49% myositis). Regarding the different SSc complications in treated patients the most frequent were digestive involvement, arthritis and interstitial lung disease (78%, 73%, and 63% respectively). 12% of patients developed cancer and 25% died during the follow-up. The most frequent indication IVIG was myositis (51%) followed by cutaneous (17%). The mean of cycles was 10. 37% of patients had previously undergone treatment with biological therapy, being RTX the most used therapy. 80% of patients had a history of use with corticosteroid therapy. When evaluating the degree of skin involvement (mRSS) patients showed a significant improvement of -2.89 ± 5.2(p <0.03) at the end of the follow-up. Indeed we observed better results in the groups of patients with myositis. No differences were observed in the% FVC or% DLCO outcomes during the follow-up. However, when we compared patients with or without overlap syndrome we found differences in%FVC values at the beginning of the study that were not present at the end of the follow-up. Patients with antiScl70 seemed to have less response to IVIG therapy. Conclusion: Our results suggest that IVIG can be useful for the management of some conditions in specific profiles of patients with SSc. Prospective studies and randomized clinical trials are necessary to establish the efficacy and safety of IVIG to treat the different conditions of SSc. Disclosure of Interests: Jose Luis TANDAIPAN JAIME: None declared, Alfredo Guillén del Castillo : None declared, Carmen Pilar Simeón-Aznar: None declared, Patricia Carreira: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Jose M Pego-Reigosa: None declared, Rosario Garcia de Vicuna Grant/research support from: Abbvie, BMS, Lilly, MSD, Novartis, Roche, Consultant for: Biogen, BMS, Mylan, Pfizer, Sanofi and Sandoz, Speakers bureau: BMS, Pfizer, Lilly, Sandoz, Anna Pros: None declared, Carlos De la Puente Bujidos: None declared, Vera Ortiz-Santamaria Speakers bureau: GSK, Roche, Pfizer, MSD, Belén Atienza-Mateo: None declared, J Lluch Pons : None declared, Manuel Rubio-Rivas: None declared, Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and Actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND